Synthesis and characterization of ZnO@CTAB-SA polymer nanocomposites with biological and photocatalytic activity - Pamula, Uday Prakash; Rao, Tentu Nageswara; Prashanthi, Y.; Ganji, Parameswaram (Frontiers in Nanotechnology, 2025)
AimThis study explores the synthesis and characterization of ZnO-based polymer nanocomposites (ZnO@CTAB-SA) employing sodium alginate (SA) and cetyltrimethylammonium bromide (CTAB) as matrices.Material and MethodsThe composites were synthesized using an in-situ polymerization method, integrating different amounts of ZnO nanoparticles. The materials exhibited substantial antibacterial effectiveness against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative), in addition to antifungal activity against Aspergillus niger. Characterization methods including FTIR, PXRD, SEM, and EDAX validated the structural integrity and efficient dispersion of ZnO nanoparticles within the polymer matrix. Furthermore, the composites demonstrated improved photocatalytic degradation of commercial dyes, such as Rhodamine B and Alizarin Red S, facilitated by adsorption and surface contacts.Results and DiscussionThese results exhibit ZnO@CTAB-SA nanocomposites as a promising multifunctional material for biomedical antibacterial approaches.ConclusionCTAB and ZnO nanoparticles enhance the composite structure and microbial cell contact, leading to increased bioactivity. These nanocomposites effectively degrade commercial dyes like Rhodamine B and Alizarin Red S through photocatalysis, indicating their potential for wastewater treatment.